Pengaruh Kualitas E-LAPOR terhadap Kepuasan Mahasiswa Administrasi Negara Universitas Tidar - Zagar Syafalah; Arina Manasikana; Raafi Grio; Nila Rifki; Desy Listiyaningrum (ANTASENA: Governance and Innovation Journal, 2026)
This study aims to analyze the effect of E-LAPOR service quality on the satisfaction level of students in the Public Administration Study Program, class of 2024, at Universitas Tidar. A quantitative approach was employed in this study, with data collected through questionnaires distributed to 109 respondents determined using the Slovin formula based on the total registered student population. The analytical framework is grounded in two main theories, namely the DeLone and McLean Information System Success Model and Customer Satisfaction Theory, which serve as the basis for measuring the dimensions of information system service quality and user satisfaction. The findings indicate that E-LAPOR service quality has a positive and significant effect on student satisfaction. However, the magnitude of the effect found is still considered moderate, suggesting that user satisfaction is not solely determined by the quality of the system's services, but is also influenced by other factors such as users' initial expectations, prior interaction experience, and students' level of digital literacy.Descriptively, the E-LAPOR platform is considered quite helpful for students in submitting aspirations and complaints to the university. Nevertheless, there are several obstacles that require serious attention, particularly regarding system access speed, the accuracy of information displayed, and the assurance of user data security. Therefore, continuous improvement and development are necessary so that E-LAPOR can operate more optimally in meeting user expectations while encouraging broader and more meaningful public participation.